Case report of a myxoma in a gamecock - Yaman, I; Durgun, T; Karabulut, E (Czech Academy Agricultural Sciences, 2004)
A mass was detected on the right side of the crop of a 17-month-old gamecock. Macroscopically, the excised mass, 10 x 7.0 x 4.0 cm in size, was ovoid-shaped with a smooth surface and a few lobules. Microscopically, the individual neoplasm cell was stellate or fusiform in shape and the cell nucleus was round, ovoid or elongated, with multiple nucleoli. No hypercellular or pleomorphic areas were identified and no mitoses were observed. The mass was myxoma according to the macroscopic and microscopic results of this study.
Keywords: myxoma; gamecock